The God of Thieves: Hermes and the Philosophy of the Improper - Grassi, Martín (2022)
In this philosophical essay, I intend to understand hermeneutics as a philosophical tradition that favors the idea of exchange and impropriety over the ideas of ownership and identity. To this end, I will explore the mythological figure of Hermes, the Greek god that was the patron of merchants, travelers, translators, and also of thieves. Attending to the idea of robbery, and opposing the notion of use against the one of ownership, I argue that a philosophy that focus on interpretation and on texts leads to acknowledge that there is nothing proper to anything nor anyone, but that propriety is but the outcome of a negotiation, of an exchange, of mutual dis-appropriations.